Materials used to support cognitive behavioural therapy for depression: a survey of therapists' clinical practice and views. Issue 6 (2nd November 2019) - Tallon, Debbie; McClay, Carrie-Anne; Kessler, David; Lewis, Glyn; Peters, Tim J.; Shafran, Roz; Williams, Chris; Wiles, Nicola
ABSTRACT: Use of supporting materials in cognitive behavioural therapy (CBT) is widely advocated, and homework increases effectiveness. The study aimed to identify materials most frequently used by CBT therapists to support CBT for depression, and those perceived clinically most effective. Questionnaires were sent to 3665 accredited CBT therapists asking about their use of resources commonly described in CBT manuals, and their views on effectiveness. Of 3665 approached by post/email, 994 (27%) responded. Another 33 completed the questionnaire via the study website. 818/1027 (80%) of respondents were accredited practitioners who deliver one-to-one therapy. Symptom measures, lists of problems/goals, activity schedules, behavioural activation diaries/plans, and case formulation worksheets were used "frequently" or "very frequently" by over 85% of respondents. Sleep diaries and computerised CBT were used least. Most resources were used within and between sessions. Activity schedules, behavioural activation diaries/plans, case formulation worksheets, thought records, and resources to support the identification of conditional beliefs were regarded as most effective. Symptom measures, sleep diaries, and computerised/online materials were considered only moderately effective. Therapists use a wide range of materials to support individual CBT. For delivering CBT, technology-enabled approaches should incorporate a range of materials to enable therapists to tailor treatment effectively.